The possibilities of fluorescence study for pre-histological endoscopic diagnosis of malignant polyp adenoma (case report) - А. А. Sokolov; А. А. Razgivina; А. V. Volova (Biomedical Photonics)
The results of fluorescence diagnosis with alasens in patient with sigmoid polyps are represented in the article. Fluorescence study gave a suspicion of malignant transformation in one of polyps. According to morphological data there was a well-differentiated colon adenocarcinoma with underlying tubular adenoma in suspicious region. Thus, fluorescence data showed malignant tumor prior to routine histological study, which was misdiagnosed for routine colonoscopy and biopsy without fluorescence diagnosis.